“Veterinary medicine is not finished when I have diagnosed an incurable disease, that’s when it starts for me.” A qualitative interview study with small animal veterinarians on hospice and palliative care - Springer, Svenja; Axiak Flammer, Shannon; Dürnberger, Christian (Frontiers in Veterinary Science, 2024)
In the wake of recent medical developments in small animal practice, curing animals of their illnesses and restoring their health can be realized better than ever before. However, the growing medical possibilities are also leading to an increase in demand for better care for patients suffering from terminal illnesses. Consequently, the field of animal hospice and palliative care has become increasingly available, enabling veterinarians to optimize the quality of life of patients, such as dogs and cats, who no longer have a prospect of full recovery. Using qualitative, semi-structured interviews with 20 small animal veterinarians involved in hospice and palliative care, we investigated the factors that motivate veterinarians to become involved in hospice and palliative care and explored the importance of relationships, communication, time and infrastructure in this area. Findings show that personal experiences with their own pets or during training or work life motivated veterinarians to provide this service. Although veterinarians highlighted the importance of empathetic-driven relationships, they were aware that keeping an emotional distance from the patient and caregiver is significant to provide successful care. Further, veterinarians emphasized their high investment of time that resulted primarily from the increased frequency and provided opportunities to communicate with caregivers. The overall conclusion is that having time for patients and the patients’ caregivers is one of the most important aspects of work in this field. However, as it will be also shown, veterinarians must consider aspects of self-care management by reflecting on their own time and energy resources while caring for animals and their caregivers.